Climate Change and Current Challenges for Landscapes and Cultural Heritage (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Landscapes and cultural heritage have faced many challenges over time, including modifications and degradation that appear with time, overlaps with other challenges not previously observed, and the influence of cities and management. One of the most visible and globally discussed challenges is climate change. Therefore, there is an urgent need to launch initiatives to tackle climate change and other current challenges from the perspective of landscape and cultural heritage protection. This Special Issue presents selected papers of studies conducted in relation to the 28th Conference on the Series of Garden Art and Historical Dendrology entitled “Climate Change and Current Challenges for Landscapes and Cultural Heritage” that was held on 28 and 29 October 2021. This collection serves as a platform for the exchange of experiences among researchers from different scientific domains.